A Region within the RAP74 Subunit of Human Transcription Factor IIF Is Critical for Initiation but Dispensable for Complex Assembly - Ren, Delin (American Society for Microbiology, 1999)
Human transcription factor IIF (TFIIF) is an α(2)β(2) heterotetramer of RNA polymerase II-associating 74 (RAP74) and RAP30 subunits. Mutagenic analysis shows that the N-terminal region of RAP74 between L155 (leucine at codon 155) and M177 is important for initiation. Mutants in this region have reduced activity in transcription, but none are inactive. Single amino acid substitutions at hydrophobic residues L155, W164, I176, and M177 have similar activity to RAP74(1–158), from which all but three amino acids of this region are deleted. Residual activity can be explained because each of these mutants forms a complex with RAP30 and recruits RNA polymerase II into the preinitiation complex. Mutants are defective for formation of the first phosphodiester bond from the adenovirus major late promoter but do not appear to have an additional significant defect in promoter escape. Negative DNA supercoiling partially compensates for the defects of TFIIF mutants in initiation, indicating that TFIIF may help to untwist the DNA helix for initiation.